Analisa Strategi Pemasaran Online Terhadap Kinerja Keuangan Umkm Fashion di Kota Bandung : ( Masa Covid-19 Januari s/d Maret 2020) - Gunardi; Rahayu, Agus; Wibowo, Lili Adi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
Creative industries, especially SMEs (Micro,Small and Medium Enterprises) in the city of Bandung duringthe Covid-19 pandemic experienced a sharp decline in sales, this Fashion MSMEs need an OnlineMarketing Strategy to maintain sales and support the government movement PSBB (Large SocialRestriction), so this will have a positive impact in improving the SMEs Financial Performance. This studyuses a Qualitative Descriptive approach by interviewing and collecting data from SMEs Fashion inBandung City, taking research data during the economic situation of Bandung, in particular, being weakand generally the world because of the Pandemic Covid-19. The results showed that the marketingstrategies carried out by Fashion MSMEs in Bandung were carried out by means of online marketing, thishad a positive impact in boosting the financial performance of Fashion SMEs in Bandung.